ORGANOLEPTIK TEPUNG KELADI ( Xanthosoma Sagittifolium) DARI HASIL FERMENTASI RAGI TAPE, RAGI ROTI DAN BAKTERI ASAM LAKTAT - Pricilia, Putri Alya (Jurnal Sains dan Teknologi Pangan, 2016)
Xanthosoma sagittifolium is local food that has not been utilized optimally and can be used as raw material for substitution of wheat flour. The aim of this study was to determine the best organoleptic characteristics of the modified Xanthosoma sagittifolium flour fermented tape and bread yeast and lactic acid bacteria. This study used a completely randomized design with two factorial ie. one factor, the use of three types of yeast namely tape yeast (F1), bread yeast (F2) and lactid acid bacteria (F3). The second factor, the time of fermentation namely one day (T1), two days (T2), three days (T3). The results showed that the sweet bread products produced with the highest score of preferred are 3,93%, 3,84% and 3,80% for color, aroma and flavor, respectively on substitution treatment of Xanthosoma sagittifolium flour with wheat flout modified lactic acid bacteria (70%:30%).